Degree of fetal growth restriction associated with schizophrenia risk in a national cohort. Issue 10 (October 2013) - Eide, M. G.; Moster, D.; Irgens, L. M.; Reichborn-Kjennerud, T.; Stoltenberg, C.; Skjærven, R.; Susser, E.; Abel, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Accumulating evidence suggests that fetal growth restriction may increase risk of later schizophrenia but this issue has not been addressed directly in previous studies. We examined whether the degree of fetal growth restriction was linearly related to risk of schizophrenia, and also whether maternal pre-eclampsia, associated with both placental dysfunction and poor fetal growth, was related to risk of schizophrenia. Method A population-based cohort of single live births in the Medical Birth Registry of Norway (MBRN) between 1967 and 1982 was followed to adulthood (n = 873 612). The outcome was schizophrenia (n=2207) registered in the National Insurance Scheme (NIS). The degree of growth restriction was assessed by computing sex-specific z scores (standard deviation units) of 'birth weight for gestational age' and 'birth length for gestational age'. Analyses were adjusted for potential confounders. Maternal pre-eclampsia was recorded in the Medical Birth Registry by midwives or obstetricians using strictly defined criteria. Results The odds ratio (OR) for schizophrenia increased linearly with decreasing birth weight for gestational age z scores (p value for trend = 0.005). Compared with the reference group (z scores 0.01–1.00), the adjusted OR [95% confidence interval (CI)] for the lowest z-score category (< − 3.00) was 2.0 (95% CI 1.2–3.5). A similar pattern was observed for birth length for gestational age z scores. Forty-nine individuals with schizophrenia were identified among 15 622 births with pre-eclampsia. The adjusted OR for schizophrenia following maternal pre-eclampsia was 1.3 (95% CI 1.0–1.8). Conclusions Associations of schizophrenia risk with degree of fetal growth restriction and pre-eclampsia suggest future research into schizophrenia etiology focusing on mechanisms that influence fetal growth, including placental function.